Case Report: Rare percutaneous coronary intervention for “right” main bifurcation - Su, Po-Hsueh; Ko, Cheng-Yu; Lee, Cheng-Han (Frontiers in Cardiovascular Medicine, 2023)
We presented the case of a patient with non-ST-elevation myocardial infarction with coronary arteries of an anomalous origin, an interarterial course of the LMCA, a unique wide-angle “right” main bifurcation lesion, and a high SYNTAX score. Management with contemporary PCI and imaging may be an alternative to surgery.